Family-School Partnership in Supporting Level 4 Students at a Community Education and Training College - Shelembe, Vumelani Mthobisi; Sedibe, Mabatho; Maseko, Nonhlanhla Desiree (Central European Journal of Educational Research, 2025)
Family-school partnership is essential for achieving quality school and academic performance to level 4 students at a Community Education and Training (CET) College. The partnership comprises the ability of families and schools to provide holistic support and guidance to students as they progress toward independence and becoming responsible community members themselves. However, this is not prevalent in the majority of CET centres, particularly those in low-income communities (Madzinga, 2021). This study explored the role of different stakeholders within the CET Colleges in enhancing family-school partnership and supporting level 4 students. The current study intends to assist schools/centres with strategies that could be used by the centres to involve families and communities to enhance the academic performance of students in the CET College. This study was underpinned by the interpretivism paradigm. Data was gathered using semi-structured individual interviews. Epstein’s model of school, family, and community interaction served as the foundation for the study. The idea was deemed appropriate for this study because it promotes parental and family involvement through mutual collaboration among many stakeholders. The findings of this study show that families want to be involved in their children’s education, but they don’t have the time owing to various commitments.